Kinetic study for Ultrasonic assisted Membrane Anaerobic System (UMAS) treating decanter Palm Oil Mill Effluent (POME) - Mansor, U. Q. A.; Ahmad Yusri, Ismail; Asdarina, Yahya; N. F. A., Shafie; Ayub Md, Som; Nour, A. H.; R. M., Yunus (UiTM Press, 2017)
The discharge of Palm Oil Mill Effluent (POME) to river or sewage causes serious environmental problem and the use of Ultrasonic-assisted Membrane Anaerobic System (UMAS) is recommended as a solution. However, further use of UMAS in treating POME tends to give blockage on the membrane surface. Monod Model kinetic parameters of control, reacted and permeate samples of POME which contribute to membrane fouling were investigated. In this study, the treatment was operated in 5 hours at which three hours treatment was with ultrasonic application. The results show that the permeate sample has the lowest maximum specific growth rate, µmax which indicates the higher amount of biomass in UMAS reactor. The amount of biomass in UMAS was increased by using ultrasonic application which prevents the membrane from fouling problem. Therefore, it is recommended to employ UMAS in POME treatments.